Innovations in Nursing Education : Simulation-Based Training for Clinical Skills Development - Vannak Pheak; Sreyneang Khun; Vuthy Sambath (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Abstract: This article explores the role of simulation-based training in enhancing nursing education, particularly in the development of clinical skills. By reviewing current trends in nursing education, the research highlights how simulation technologies, such as high-fidelity mannequins and virtual simulations, offer realistic and risk-free environments for nurses to practice critical skills. The findings suggest that simulation-based training improves competence, confidence, and readiness for real-world clinical situations, contributing to the development of highly skilled and prepared nurses.